Visual sociology - Zuev, D.; Krase, J. (Sociopedia.isa, 2017)
The article offers an overview of the field of visual sociology. It examines the areas where visu- al sociology can provide an insightful perspective for the study of social reality and serves as an imagina- tive tool to work with a variety of research subjects. It outlines some specific methods for working with visual data and focuses on a few of the many fields where visual sociological methods can fruitfully be applied, such as the study of cities, public events and new media.